Laboratory Simulations of Plasma Generated Around the Atmospheric Reentry Spacecraft - Abdulmuttaleb, Nabaa Ahmed; Yaseen, Waleed Ibrahim (Iraqi Journal of Science, 2024)
In this paper, plasma will be generated in a laboratory as a simulation of what happens to spacecraft when they enter the atmosphere of Earth. Parameters of plasma generation were determined in terms of pressures of 0.1, 0.2, 0.3, 0.4, and 0.5 mbar and generation energy 200 W. The parameters of the generated plasma were calculated using the optical emission spectroscopy two intensity ratio method, and the electron temperature, electron density, Debye length, and plasma frequency were calculated. Compare the results with the actual results, electron temperatures were 2.26–1.71 eV and plasma frequency 8.09 x1011-6.7x1011 at 0.1-0.5 mbar pressure.